Association of age with risk of first and subsequent allograft failure and mortality among young kidney transplant recipients in the USA – a retrospective cohort study. (5th October 2020) - Okuda, Yusuke; Streja, Elani; Rhee, Connie M.; Tantisattamo, Ekamol; Reddy, Uttam; Laster, Marciana; Tang, Ying; Rajpoot, Deepak; Molnar, Miklos Z.; Ichii, Hirohito; Obi, Yoshitsugu; Kalantar‐Zadeh, Kamyar
Summary: Adolescent age may be a high‐risk period for kidney allograft failure. However, the knowledge on this topic is limited mostly to the first transplant. Among 20 960 patients aged ≤21 years at the first kidney transplantation from the US Renal Data System, we evaluated the association of age at the first kidney transplant with risk for the first and subsequent graft failures (1st, 2nd, and 3rd) using the conditional risk set model for recurrent time‐to‐event data. The median age was 15 (interquartile range: 9–18) years, and 18% received transplants twice or more during a median follow‐up of 9.7 years. The risk for graft failures was highest in 16 to <18 years old with an adjusted hazard ratio (aHR) of 1.93 (95% CI, 1.73–2.15; reference: <3 years). When separately analyzed, the highest risk was observed in 17, 19, and 21 years old for the first, second, and third transplant, respectively. Those 16 to <18 years were also strongly associated with the highest risk for death after returning to dialysis (aHR, 4.01; 95% CI, 2.82–5.71). Adolescent recipients remain at high risk for allograft failure for a long time, which may result in high mortality risk, even though they surpass this high‐risk period soon after the first transplant.